The ADAMTS2 metalloproteinase inhibits tumor growth by regulating the innate immune system - Loïc Joannes; Laura Dupont; Louis Stock; Esther Arpigny; Pascale Hubert; Marie Ancion; Margaux Luyckx; Joan Abinet; Wen Peng; Didier Calaldo; Agnes Noel; Thomas Marichal; et al. (Cancer Cell International)
Abstract Background ADAMTS2 is a metalloproteinase known to be implicated in collagen maturation and regulation of (lymph)angiogenesis. As these properties are likely to alter tumor progression, we aimed to assess the overall impact of ADAMTS2 on cancer development. Methods and results Using publicly available human cancer datasets, we found that high expression of ADAMTS2 in primary tumors is associated with poor prognosis across various cancer types. Similar analyses were repeated, but this time using the ratio of ADAMTS2 on COL1A1 expression to take into account potential biases due to the involvement of ADAMTS2 in collagen fibril formation. Remarkably, these data indicate that patients with a high ADAMTS2/COL1A1 ratio exhibit an improved overall survival rate, suggesting that ADAMTS2 may inhibit cancer progression by a mechanism independent of collagen accumulation. This hypothesis was evaluated in vivo using ADAMTS2-KO mice and different tumor models characterized by the absence or presence of tumor collagen accumulation, as in MMTV-PyMT mice which develop spontaneous desmoplastic mammary tumors. In all the models, the growth of primary tumors was strongly increased in ADAMTS2-KO mice versus their wild type counterparts, confirming that ADAMTS2 displays anti-tumor properties. In stark contrast, the spread of lung metastases from mammary tumors was virtually prevented in ADAMTS2-KO mice, showing a dual role of ADAMTS2, either beneficial or detrimental, at different stages of cancer progression. Additional investigations, notably by FACS and single cell sequencing, showed that the effect of ADAMTS2 on primary tumors does not result from a direct effect on cancer cells, but rather from modifications in the intratumor innate immune system which becomes more immunosuppressive in the absence of ADAMTS2. Conclusion We have shown that ADAMTS2 suppresses tumor growth by inhibiting the progressive establishment of an immunosuppressive microenvironment. Conversely, its presence allows efficient formation of lung metastases. These data identify ADAMTS2 as a cancer regulator with antagonistic functions, limiting initial progression but promoting efficient metastatic dissemination.